Cover Feature: Are the Accompanying Cations of Doping Anions Influential in Conducting Organic Polymers? The Case of the Popular PEDOT (Chem. Eur. J. 63/2019). Issue 63 (30th September 2019) - Fuentes, Isabel; Mostazo‐López, María José; Kelemen, Zsolt; Compañ, Vicente; Andrio, Andreu; Morallón, Emilia; Cazorla‐Amorós, Diego; Viñas, Clara; Teixidor, Francesc
Abstract : Conducting organic polymers (COPs) display attractive electrical properties, which can be modified with tuning. To this purpose, elaborate and sometimes cumbersome chemical modifications on the monomer are done. This work demonstrates a simple and efficient way to achieve such a tuning, just by focusing on the accompanying cations of the doping anions [Co(C2 B9 H11 )2 ] − . These have been shown to be non‐innocent in the conducting organic polymer prepared with the monomer EDOT and the metallacarborane [Co(C2 B9 H11 )2 ] − . The accompanying cations determine the stoichiometries of the COPs, and the stoichiometries in turn influence the electrochemical properties. More information can be found in the Full Paper by F. Teixidor et al. on page 14308 .